PERFORMA BAHASA DAN KESANTUNAN KOMUNIKASI LISAN PEJABAT LEGISLATIF DAN TOKOH PARTAI TINGKAT KABUPATEN DI SUMATRA BARAT - Nurani, Sri; Ermanto, Ermanto (Universitas Negeri Padang, 2019)
This study aims to describe: (1) the performance of formal sentence structures in oral communication of district-level legislative and party leaders in West Sumatra, (2) standard vocabulary performance in verbal communication at district level legislative and party leaders in West Sumatra, (3) the principle performance of courtesy in oral communication of district-level legislative and party leaders in West Sumatra; and (4) the performance of the principle of cooperation in the oral communication of district-level legislative and party leaders in West Sumatra. This type of research is qualitative research with descriptive methods. The data of this study are the utterances of legislative and party leaders in West Sumatra in oral communication. The methods and data collection techniques used are the referral method, with advanced techniques, namely the note-taking technique. The technique of validating data is a detailed description technique, namely describing in detail the data to be interpreted. Data analysis methods and techniques are carried out by identifying data, transcribing, entering data into a format, classifying data, interpreting data, and concluding data. Based on the results of research and discussion, it can be concluded the following matters. (1) The performance of the use of formal sentence structures in oral communication of district legislators and party leaders in West Sumatra is quite sufficient (66%) of 150 data. West Sumatra is quite sufficient (66.7%) of 150 data. (3) The performance of the principle of manners in oral communication of legislative officials and party leaders at the district level in West Sumatra, the principle of courtesy is quite sufficient (67.3%) of 150 data. (4) The performance of the principle of cooperation in oral communication of legislative officials and district leaders in West Sumatra is classified as good (81.3%) of 150 data.Â Keywords: Performance, Oral Communication, Legislative Officials, Party LeadersÂ